Fatty acid composition of total lipids and phospholipids of muscular tissue and brain of rats under the impact of vibration - N. M. Kostyshyn; M. R. Grzegotsky; J. F. Rivis (Zaporožskij Medicinskij Žurnal)
Fatty acids are important structural components of biological membranes, energy substrate of cells involved in fixing phospholipid bilayer proteins, and acting as regulators and modulators of enzymatic activity. Under the impact of vibration oscillations there can occur shifts in the ratio of different groups of fatty acids, and degrees of their saturation may change. The imbalance between saturated, monounsaturated and polyunsaturated fatty acids, which occurs later in the cell wall, disrupts fluidity and viscosity of lipid phase and causes abnormal cellular metabolism.